Association among Neck Circumference and Percent Body Fat with Fasting Blood Glucose in Obese Female College Students - Fillah Fithra Dieny; Iin Indartiningsih; Nuryanto Nuryanto; Ayu Rahadiyanti (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
Background: Neck circumference could describe upper-body subcutaneous fat, correlated with obesity and diabetes mellitus.Objective: The purpose of this study was to determine the correlation between percent body fat and neck circumference with fasting blood glucose in obese female college students.Methods: The study was cross-sectional, conducted at Diponegoro University in June-August 2019. 119 participants were female, aged 17-21 years selected using the purposive sampling method. Measurement of waist circumference was used as an indicator of obesity. Percent body fat was measured using Bioelectrical Impedance Analysis (BIA), and neck circumference was measured using a met line. Fasting blood glucose was examined after the subject fasted for 8-12 hours, the amount of blood taken was 5 cc. Data were analyzed with the Rank-Spearman correlation test.Results: As many as 84% of subjects had excess percent body fat. The median neck circumference was 32.5 cm. The median fasting blood glucose was 87 mg / dL. There was a significant correlation between percent body fat with fasting blood glucose (r = 0.231) (p = 0.012). There was no correlation between neck circumference with fasting blood glucose (r = 0.137) (p = 0.137).Conclusion: Percent of body fat had a significant relationship with fasting blood glucose, and the greater the circumference of the neck, the greater fasting blood glucoseKeywords: Obesity, Neck Circumference, Percent Body Fat, Fasting Blood Glucose